Photocatalytic material based on CuInZnS quantum dot-carbon nano bowl composite structure and preparation and magnetic field auxiliary application thereof
Through the composite structure and magnetic field assist technology of CuInZnS quantum dots and carbon nanobowls, the limitations of existing photocatalytic materials in carrier separation and cost are solved, and efficient photocatalytic hydrogen production performance and material cost reduction are achieved.
Patent Information
- Application Number
- CN202411524852.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
Existing semiconductor photocatalytic materials have limitations in improving light absorption efficiency and carrier separation efficiency, especially in efficient separation of photogenerated carriers and reducing material costs.
The composite structure of CuInZnS quantum dots and carbon nanobowls is adopted to improve the photogenerated carrier utilization rate of CuInZnS materials through the conductivity of the carbon nanobowl and the micro-nano current collector, and further promote carrier separation and migration through magnetic field assist technology. .
It significantly improves the photocatalytic hydrogen production performance, reduces material costs, and achieves efficient carrier separation and migration, improving the overall efficiency of the photocatalyst.
Smart Images

Figure CN119386896A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite photocatalytic material based on CuInZnS quantum dot-carbon nanobowl and a preparation method and magnetic field-assisted application thereof, belonging to the technical field of photocatalytic materials. Background Art
[0002] As a potential technology in the field of clean energy production, semiconductor photocatalytic hydrogen evolution technology is attracting widespread attention. In order to improve its photocatalytic performance, researchers have conducted in-depth research on various methods, focusing on improving the efficiency of solar light absorption and optimizing the carrier separation process. Although progress has been made in improving light absorption, suppressing the recombination of photogenerated carriers remains a key issue that needs to be addressed. Therefore, strengthening the effective separation of photoinduced electrons and holes is particularly important in photocatalytic reactions.
[0003] Constructing semiconductor heterojunctions, such as those based on Schottky heterojunctions, pn junctions, and structures designed by band structure matching, is an important means to improve the efficiency of carrier separation. These heterostructures can form a built-in electric field at the interface, which helps to separate carriers. However, due to the inherent properties of semiconductor materials, the efficiency of this method is relatively limited.
[0004] In recent years, researchers have begun to explore the application of external fields / forces to regulate the separation and migration of photoinduced carriers. By applying an external electric field to the electrode, the number of photogenerated carriers can be significantly increased. However, this solution requires that the photocatalyst must have good conductivity and semiconductor properties and must be loaded on the electrode, which limits the thickness of the catalyst layer. At the same time, the need for an external circulation circuit increases the complexity of the system and limits the loading amount of the photocatalyst. Although the photoelectrochemical efficiency has been improved, the overall photocatalytic efficiency is still insufficient.
[0005] For highly active powder photocatalysts, since they cannot be connected to an external circuit, a new way to separate photogenerated carriers is needed. In addition to the photoelectrochemical process, researchers have also proposed the strategy of wireless radio fields, but they face huge challenges in practical applications. Fortunately, some nanomaterials can generate electric potential under specific conditions, and after combining with photocatalysts, they can be dispersed in water as a source of accompanying electric potential.
[0006] Magnetic field induced current is widely used in daily life, and nanomaterials that can generate magnetic potential are expected to become an ideal choice for providing wireless fields. According to Faraday's electromagnetic induction principle, metal-based nanomaterials can generate induced electromotive force when moving perpendicular to the direction of the magnetic field. However, metal-based materials are expensive and easy to corrode, and the high weight ratio in the composite material reduces the content of active photocatalysts, limiting their practical application in magnetic field photocatalytic hydrogen evolution. For this reason, traditional carbon materials such as graphene, carbon nanofibers and carbon nanotubes have been developed and combined with semiconductor photocatalysts to improve the performance of magnetic field photocatalytic hydrogen evolution. For example: The inventor of the present invention's previous patent document CN116851007A discloses the preparation and magnetic field-assisted photocatalytic application of carbon nanotube-indium zinc sulfide nanosheet composite materials, which composites the conductor material carbon nanotubes and the semiconductor photocatalyst indium zinc sulfide to form a conductor-semiconductor composite structure, and constructs a magnetoelectric photocatalytic material assisted by a built-in electric field and an external magnetic field.
[0007] However, the cost of semiconductor material indium is relatively high, and reducing the proportion of indium per unit mass of material and thus reducing costs has become a new challenge. Compared with traditional carbon materials such as graphene, carbon nanofibers and carbon nanotubes, new bowl-shaped carbon materials (Carbon Bowls) have shown remarkable results and obtained impressive experimental results in the field of composite photocatalysis due to their unique nanostructure and excellent electrical conductivity. The present invention uses a new bowl-shaped carbon material as a component of a composite photocatalyst, and integrates it into a magnetic field regulation system for photocatalytic water decomposition and hydrogen evolution reaction. Upon searching, no precedent has been found for combining bowl-shaped carbon materials with semiconductor photocatalysts to achieve a high photogenerated carrier separation rate and optimize photocatalytic performance. For this reason, the present invention is proposed. Summary of the invention
[0008] In view of the deficiencies of the prior art, the present invention provides a composite material based on CuInZnS quantum dots-carbon nano bowls. The material is constructed from a carbon bowl (CB) and a semiconductor photocatalyst (CuInZnS quantum dots) to form a conductor-semiconductor composite structure, which can construct a magneto-electric photocatalytic material system assisted by a built-in electric field and an external magnetic field. In the composite material, the CuInZnS quantum dots are loaded on the surface of the bowl-shaped carbon material, and the carbon bowl plays the role of a micro-nano current collector, which can improve the utilization rate of the photogenerated carriers of the CuInZnS material and obtain enhanced photocatalytic hydrogen production performance.
[0009] The technical solution of the present invention is as follows:
[0010] A photocatalytic material based on a CuInZnS quantum dot-carbon nanobowl composite structure. The photocatalytic material is a composite structure material constructed of a carbon nanobowl and a semiconductor photocatalyst CuInZnS quantum dots, and the CuInZnS quantum dots are loaded on the surface of the carbon nanobowl.
[0011] According to the present invention, preferably, the diameter of the CuInZnS quantum dots is 30-60 nm, the inner diameter of the carbon nanobowl is 180-220 nm, and the outer diameter is 200-250 nm.
[0012] According to the present invention, preferably, the mass ratio of CuInZnS quantum dots to carbon nanobowls in the composite structural material is (13-15):1.
[0013] According to the present invention, preferably, the carbon nanobowl is based on silicon dioxide as a carrier, carbonized in a N2 atmosphere at 800°C for 4 hours, and then reacted with a 20wt% HF solution for 24 hours to remove silicon dioxide, and nitrogen-doped carbon nanobowl powder is obtained after drying.
[0014] According to the present invention, the method for preparing the above-mentioned photocatalytic material based on the CuInZnS quantum dot-carbon nanobowl composite structure comprises the following steps:
[0015] (1) Dissolve ZnCl2 in a mixed solvent of H2O and C2H5OH, mix well and add the carbon nanobowl, and soak the carbon nanobowl in the ZnCl2 solution for 24 hours; the purpose of this process is to dissolve Zn 2+ Embedding in the lattice of the carbon nanobowl is conducive to the loading of CuInZnS quantum dots on the surface of the carbon nanobowl and reducing the free CuInZnS;
[0016] (2) washing the carbon nanotubes soaked in step (1) repeatedly by centrifugation with water and ethanol, and vacuum drying;
[0017] (3) adding the carbon nanotube obtained in step (2) to a mixed solution of CuCl2·2H2O, InCl2·4H2O and TAA, and uniformly dispersing by ultrasonication; preferably, the solvent is H2O;
[0018] (4) adjusting the pH of the suspension obtained by uniformly dispersing in step (3) to 8.5 by adding NaOH solution;
[0019] (5) The suspension obtained in step (4) is transferred to an autoclave for a hydrothermal reaction. After the hydrothermal reaction is completed, the solution is naturally cooled to room temperature. The reaction product is centrifuged to obtain a precipitate. The precipitate is washed with water and ethanol and vacuum dried to obtain a photocatalytic material based on a CuInZnS quantum dot-carbon nanobowl composite structure.
[0020] According to the present invention, preferably, in step (3), the molar ratio of CuCl2·2H2O, InCl3·4H2O and TAA is 1:(1.9-2.0):(6-7).
[0021] According to the present invention, preferably, the amount of carbon nanotubes added is controlled at 5wt%-10wt% of CuInZnS quantum dots, and most preferably 7wt%.
[0022] According to the present invention, preferably, the hydrothermal reaction temperature in step (5) is 100-120° C.; preferably, the reaction time is 3-5 h.
[0023] According to the present invention, a method for preparing a photocatalytic material based on a CuInZnS quantum dot-carbon nanobowl composite structure, a preferred embodiment, comprises the following steps:
[0024] ZnCl2 (230 mg) was dissolved in a mixed solvent of 10 ml H2O and 10 ml C2H5OH, and stirred for 10 min until it was completely dissolved; carbon nanotubes were added to the mixed solvent, and ultrasonic treatment was performed for 30 min to obtain a suspension. After soaking for 24 h, the suspension was repeatedly centrifuged and washed, and dried to obtain Zn 2+ Embedded carbon nanobowl; then, CuCl2·2H2O (123.3 mg), InCl3·4H2O (413.9 mg) and TAA (363.5 mg) were dissolved in H2O (10.0 mL) in sequence and stirred for 10 min until all dissolved; the treated carbon nanobowl was added to the mixed solvent, ultrasonically treated for 30 min to obtain a suspension, and the pH was adjusted to 8.5 by NaOH (1 mol) solution; the adjusted suspension was transferred to a 50 mL teflon autoclave and heated at 110 ° C for 4 h; after the reaction, the solution was naturally cooled to room temperature and the mixture was heated at 10000 rpm min -1 After centrifugation for 10 min, a precipitate was obtained, which was then thoroughly washed with water and ethanol and dried in a vacuum oven at 60° C. to obtain a photocatalytic material based on a CuInZnS quantum dot-carbon nanobowl composite structure.
[0025] According to the present invention, the above-mentioned photocatalytic material based on the CuInZnS quantum dot-carbon nanobowl composite structure is used for photocatalytic water decomposition and hydrogen evolution reaction.
[0026] According to the present invention, preferably, the application method is as follows:
[0027] The photocatalytic material based on the CuInZnS quantum dot-carbon nanobowl composite structure is dispersed in water, ascorbic acid is added, and the photocatalytic water decomposition and hydrogen evolution reaction are carried out under the conditions of rotating magnetic field and light.
[0028] Preferably, the magnetic field is a magnetic field generated by a neodymium iron ore permanent magnet, the magnetic field strength is 100 mT, the rotation speed is 350 rpm, and the light is irradiated with a 300 W xenon lamp intensity;
[0029] Preferably, the amount of the photocatalytic material based on the CuInZnS quantum dot-carbon nanobowl composite structure added is 30-50 mg / 50 mL water;
[0030] Preferably, ascorbic acid is used as a sacrificial agent and is added in an amount of 0.2-0.3 mol / L.
[0031] According to the present invention, a preferred embodiment of the application method of the CuInZnS quantum dot-carbon nanobowl composite structure photocatalytic material for photocatalytic water decomposition and hydrogen evolution reaction comprises the following steps:
[0032] In the photocatalytic reactor, 30 mg of photocatalytic material based on CuInZnS quantum dot-carbon nanobowl composite structure was dispersed in 50 mL of mixed aqueous solution containing 0.2 M ascorbic acid, and magnetic field-assisted photocatalytic hydrogen evolution reaction was carried out under 100 mT magnetic field and 300 W xenon lamp light intensity.
[0033] Beneficial effects of the present invention:
[0034] 1. The present invention constructs a conductor-semiconductor composite structure and uses cheap, low-load carbon nanobowls to construct a high-speed channel for carrier transmission between CuInZnS quantum dots to form a current collector effect for photogenerated carriers, which can greatly improve the utilization rate of photogenerated carriers of CuInZnS materials and obtain enhanced photocatalytic hydrogen production performance.
[0035] 2. In the present invention, the cost of copper is lower than that of indium. The addition of copper reduces the specific gravity of indium per unit mass of material, thereby reducing the cost.
[0036] 3. Based on the construction of built-in potential difference to promote carrier migration, the present invention introduces a magnetic field to generate motional electromotive force in the carbon nanobowl conductor through the Lorentz force and cutting of magnetic flux lines, which jointly promotes the separation and migration of semiconductor photogenerated carriers, improves the semiconductor photocatalytic performance, and achieves the effect of efficient photocatalytic water decomposition and hydrogen evolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1-2 This is a scanning electron microscope photograph of the photocatalytic material of the CuInZnS quantum dot-carbon nanobowl composite structure with a carbon nanobowl dosage of 7 wt % obtained in Example 2.
[0038] Figure 3 This is a graph showing the performance data of the photocatalytic water decomposition reaction of the CuInZnS quantum dots and 7 wt% CuInZnS quantum dots-carbon nanobowl composite structure photocatalytic materials obtained in Examples 1 and 2 in a magnetic field-assisted device. DETAILED DESCRIPTION
[0039] In order to better understand the present invention, the present invention is further described below with reference to specific embodiments and drawings, but is not limited thereto.
[0040] Unless otherwise specified, the raw materials described in the examples are conventional commercially available products.
[0041] Example 1: Preparation of CuInZnS quantum dots
[0042] Dissolve ZnCl2 (230 mg), CuCl2·2H2O (123.3 mg), InCl3·4H2O (413.9 mg) and TAA (363.5 mg) in H2O (10.0 mL) in sequence and stir for 10 min until all dissolved; adjust the pH to 8.5 with NaOH (1 mol) solution; transfer the adjusted solution to a 50 mL Teflon autoclave and heat at 110 ° C for 4 h; after the reaction, cool the solution naturally to room temperature and heat the mixture at 10000 rpm min -1 After centrifugation for 10 min, a precipitate was obtained, which was then thoroughly washed with water and ethanol and dried in a vacuum oven at 60° C. to obtain a CuInZnS quantum dot photocatalyst.
[0043] Example 2: Preparation of a photocatalytic material of CuInZnS quantum dot-carbon nanobowl composite structure with a carbon nanobowl dosage of 7 wt%
[0044] ZnCl2 (230 mg) was dissolved in a mixed solvent of 10 ml H2O and 10 ml C2H5OH, and stirred for 10 min until it was completely dissolved; carbon nanotubes were added to the mixed solvent, and ultrasonic treatment was performed for 30 min to obtain a suspension. After soaking for 24 h, the suspension was repeatedly centrifuged and washed, and dried to obtain Zn 2+ Embedded carbon nanobowl; then, CuCl2·2H2O (123.3 mg), InCl3·4H2O (413.9 mg) and TAA (363.5 mg) were dissolved in H2O (10.0 mL) in turn and stirred for 10 min until all dissolved; the treated carbon nanobowl was added to the mixed solvent, ultrasonically treated for 30 min to obtain a suspension, and the pH was adjusted to 8.5 by NaOH (1 mol) solution; the adjusted suspension was transferred to a 50 mL teflon autoclave and heated at 110 ° C for 4 h; after the reaction, the solution was naturally cooled to room temperature and the mixture was heated at 10000 rpm min -1 After centrifugation for 10 minutes, a precipitate was obtained, which was then thoroughly washed with water and ethanol and dried in a vacuum oven at 60° C. to obtain a CuInZnS quantum dot-carbon nanobowl composite structure photocatalytic material.
[0045] The scanning electron microscope photocatalytic material of the CuInZnS quantum dot-carbon nanobowl composite structure with a carbon nanobowl doping content of 7 wt% obtained in this example is shown in FIG. Figure 1-2 As shown. Figure 1-2 It can be seen that the diameter of CuInZnS quantum dots is 30-60nm, the inner diameter of the carbon nanobowl is 180-220nm, and the outer diameter is 200-250nm.
[0046] Example 3: Magnetic Field Assisted Photocatalytic Hydrogen Evolution Reaction
[0047] In the photocatalytic reactor, 30 mg of CuInZnS quantum dot-carbon nanobowl composite structure photocatalytic material was dispersed in 50 mL of mixed aqueous solution containing 0.2 M ascorbic acid, and photocatalytic water decomposition and hydrogen evolution reaction were carried out under rotating magnetic field and light conditions. The magnetic field was generated by a neodymium iron ore permanent magnet with a magnetic field intensity of 100 mT, a rotating magnetic field speed of 350 rpm, and light was irradiated with a 300 W xenon lamp intensity.
[0048] Photocatalytic test results are as follows Figure 3 As shown in the figure, CIZS represents a single CuInZnS quantum dot, CB represents a carbon nanobowl, CB-CIZS represents a CuInZnS quantum dot-carbon nanobowl composite photocatalytic material, NMF represents a condition without a magnetic field, and MF represents a condition with a magnetic field.
[0049] Depend on Figure 3 The results show that the hydrogen evolution performance of pure CuInZnS quantum dots is only 45.45 μmol·g -1 ·h -1 When the carbon nanobowl is combined with CuInZnS quantum dots, the hydrogen evolution performance of the CuInZnS quantum dots-carbon nanobowl composite photocatalytic material is only improved to 47.72 μmol·g -1 ·h -1 When a magnetic field is added, the hydrogen evolution performance of pure CuInZnS quantum dots is only improved by 11.9% compared with that in the non-magnetic condition, while the hydrogen evolution performance of CuInZnS quantum dots-carbon nanobowl composite photocatalytic material is improved by 43.2% compared with that in the non-magnetic condition.
Claims
1. A photocatalytic material based on a CuInZnS quantum dot-carbon nanobowl composite structure, characterized in that: The photocatalytic material is a composite structure material constructed of a carbon nanobowl and semiconductor photocatalyst CuInZnS quantum dots, and the CuInZnS quantum dots are loaded on the surface of the carbon nanobowl.
2. The photocatalytic material based on the CuInZnS quantum dot-carbon nanotube composite structure according to claim 1, characterized in that: The diameter of the CuInZnS quantum dots is 30-60nm, the inner diameter of the carbon nano bowl is 180-220nm, and the outer diameter is 200-250nm.
3. The photocatalytic material based on CuInZnS quantum dot-carbon nanotube composite structure according to claim 1, characterized in that: The mass ratio of CuInZnS quantum dots to carbon nanobowls in the composite structural material is (13-15):
1.
4. The photocatalytic material based on CuInZnS quantum dot-carbon nanotube composite structure according to claim 1, characterized in that: The carbon nano bowl uses silicon dioxide as a carrier, is carbonized in a N2 atmosphere at 800°C for 4 hours, and then reacted with a 20wt% HF solution for 24 hours to remove silicon dioxide, and nitrogen-doped carbon nano bowl powder is obtained after drying.
5. The method for preparing the photocatalytic material based on the CuInZnS quantum dot-carbon nanotube composite structure according to any one of claims 1 to 4, comprising the following steps: (1) Dissolve ZnCl2 in a mixed solvent of H2O and C2H5OH, mix well and add the carbon nanobowl, and soak the carbon nanobowl in the ZnCl2 solution for 24 hours; the purpose of this process is to dissolve Zn 2+ Embedding in the lattice of the carbon nanobowl is conducive to the loading of CuInZnS quantum dots on the surface of the carbon nanobowl and reducing the free CuInZnS; (2) washing the carbon nanotubes soaked in step (1) repeatedly by centrifugation with water and ethanol, and vacuum drying; (3) adding the carbon nanotube obtained in step (2) to a mixed solution of CuCl2·2H2O, InCl2·4H2O and TAA, and uniformly dispersing by ultrasonication; preferably, the solvent is H2O; (4) adjusting the pH of the suspension obtained by uniformly dispersing in step (3) to 8.5 by adding NaOH solution; (5) The suspension obtained in step (4) is transferred to an autoclave for a hydrothermal reaction. After the hydrothermal reaction is completed, the solution is naturally cooled to room temperature. The reaction product is centrifuged to obtain a precipitate. The precipitate is washed with water and ethanol and vacuum dried to obtain a photocatalytic material based on a CuInZnS quantum dot-carbon nanobowl composite structure.
6. The method for preparing a photocatalytic material based on a CuInZnS quantum dot-carbon nanotube composite structure according to claim 5, characterized in that: In step (3), the molar ratio of CuCl2·2H2O, InCl3·4H2O and TAA is 1:(1.9-2.0):(6-7).
7. The method for preparing a photocatalytic material based on a CuInZnS quantum dot-carbon nanotube composite structure according to claim 5, characterized in that: The added amount of the carbon nanobowl is controlled at 5wt%-10wt% of the CuInZnS quantum dots.
8. The method for preparing a photocatalytic material based on a CuInZnS quantum dot-carbon nanotube composite structure according to claim 5, characterized in that: The hydrothermal reaction temperature in step (5) is 100-120°C.
9. Application of the photocatalytic material based on the CuInZnS quantum dot-carbon nanobowl composite structure according to any one of claims 1 to 4 for photocatalytic water decomposition and hydrogen evolution reaction.
10. The use according to claim 9, characterized in that: The application method is as follows: The photocatalytic material based on the CuInZnS quantum dot-carbon nanobowl composite structure is dispersed in water, ascorbic acid is added, and the photocatalytic water decomposition and hydrogen evolution reaction are carried out under the conditions of rotating magnetic field and light. Preferably, the magnetic field is a magnetic field generated by a neodymium iron ore permanent magnet, the magnetic field strength is 100 mT, the rotation speed is 350 rpm, and the light is irradiated with a 300 W xenon lamp intensity; Preferably, the added amount of the photocatalytic material based on the CuInZnS quantum dot-carbon nanobowl composite structure is 30-50 mg / 50 mL water.
Citation Information
Patent Citations
Preparation of composite material based on carbon nanotube-indium zinc sulfide nanosheet and magnetic field-assisted photocatalysis application
CN116851007A